Math, asked by vidhiarmy, 5 months ago

solve any one question
urgent please help solve any one question​

Attachments:

Answers

Answered by anusheelshukla54
2

So, in these type of question you need do a simple thing which transposition.

So, First

(3xy + 5yz - 3zx ) + x = 6xy - 3yz

(5yz-3zx) + x = 6xy- 3yz - 3xy

(5yz-3zx) + x = 3xy - 3yz

-3zx + x = 3xy - 3yz  - 5yz

-3zx + x = 3xy-8yz

x = 3xy - 8yz + 3zx

Answered by SanaArmyGirl
65

Answer:

 \\  \\ hope \: it \:  \: was \: helpful \\

Attachments:
Similar questions